Next-generation sequencing analysis of cephalosporin resistant bacteria from the aquatic environment in Singapore - Zhong, Yang (Nanyang Technological University, 2023)
Based on the list of global priority pathogens (GPP) published by the World Health Organisation (WHO) in 2017, Enterobacterales resistant to carbapenems and/or 3rd generation cephalosporins has been listed as the first priority (critical) pathogen. The fast-spreading cephalosporin resistance has become a significant threat to public health. The “One Health” approach has been demonstrated as an effective approach to control resistance spread. Monitoring antimicrobial resistance (AMR) in a “One Health” approach refers to the multisector efforts to trace resistant bacteria and resistance genes transmission across different sources. As resistance can be transferred horizontally, bacteria from non-human “One-Health” sectors like food, animal and the environment also act as “reservoirs” of resistance. The collection and characterization of cephalosporin-resistant strains from healthcare settings have been done in Singapore since early 2000. Characterization of resistant strains from other “One Health” sectors like healthy people, food and animal has also been done since 2009. However, there are few investigations of resistant strains from surface water, like reservoir water. Reservoirs are the unique water storage system in Singapore which collects stormwater and stores imported water. It plays a critical role in the local freshwater supply, and bacteria in reservoirs can well represent the bacteria from the local environment. Also, there were limited “One Health” studies in Singapore accessing the diversity and relatedness of resistant strains from all available sectors, including environment, food and humans, with genomic and genetic approaches. In this study, we planned to complete a “One Health” genetic-based investigation, including the resistance bacteria from the natural water environment. We are aiming to understand the role of aquatic bacteria in resistance transmission from the “One-Health” perspective. To achieve this, we first characterized the cephalosporin-resistant bacteria from the aquatic environment with whole-genome-sequencing (WGS) and metagenomic sequencing analysis. Secondly, we pooled the WGS data of the aquatic environment isolates with strains from multiple “One-Health” sectors, including food, animal and humans, and analysis them in a systematic manner. We compared their genomic profile and described the close-related pair of strains across different sources. We further zoomed into their resistance patterns and finally investigated the mobile resistance elements shared across different sources. We reveal several main findings. Firstly, we found that cephalosporin and carbapenem-resistant bacteria were present in the reservoir water. The aquatic resistant strains shared the same sequence types (ST) as strains from the bloodstream patients. Secondly, resistant strains from different sources are distinguishable at the clonal level. Even though some close-related pairs of strains have been found across different sources, there is no direct link between aquatic strains and clinical strains. Finally, we found that resistant strains of different species from different sources contain the same conserved resistance gene clusters. The conserved resistance gene cluster was circulating among different sources and species. We postulated that this gene cluster could be used as a genetic indicator to monitor resistance transmission across different sectors.